Learning Management Model Through Teaching Factory: Implementation Strategies and Challenges - Perwita, Dyah; Widuri, Retno; Anggraeni, Oki (Universitas Negeri Semarang, 2025)
This study aims to determine the strategies and implementation challenges of learning management using the Teaching Factory model. The subjects in this research are students of vocational programs at Airlangga University (UNAIR) that serves as a comparative study for vocational program students at Jenderal Soedirman University (UNSOED). This study used a sample of 5 study programs. The approach used in this research is a case study-based qualitative approach. The findings of this research are: (1) the implementation of teaching factory in UNAIR involves several stakeholders such as students, lecturers, course coordinators in vocational programs and the World of Business and Industry; (2) the teaching factory-based learning approach can only be implemented in certain courses, not as a whole; (3) the place and service is at Airlangga Wellness Center/ AWC; (4) the strategy of offering teaching factory services is to establish it in a strategic location; (5) challenges in the implementation of teaching factory are faced by lecturers and students of vocational programs; and (6) the implementation of teaching factory has theoretical and practical benefits. This study limited in vocational programs at UNAIR and UNSOED. The future research could focus comparing the effectiveness of Teaching Factory in different vocational fields of study, such as engineering, design, and tourism in different universities.